Efficacy of early administration of escitalopram on depressive and emotional symptoms and neurological dysfunction after stroke: a multicentre, double-blind, randomised, placebo-controlled study. (January 2017) - Kim, Jong S; Lee, Eun-Jae; Chang, Dae-Il; Park, Jong-Ho; Ahn, Seong Hwan; Cha, Jae-Kwan; Heo, Ji Hoe; Sohn, Sung-Il; Lee, Byung-Chul; Kim, Dong-Eog; Kim, Hahn Young; Kim, Seongheon; et al.
Summary: Background: Mood and emotional disturbances are common in patients with stroke, and adversely affect the clinical outcome. We aimed to evaluate the efficacy of early administration of escitalopram to reduce moderate or severe depressive symptoms and improve emotional and neurological dysfunction in patients with stroke. Methods: This was a placebo controlled, double-blind trial done at 17 centres in South Korea. Patients who had had an acute stroke within the past 21 days were randomly assigned in a 1:1 ratio to receive oral escitalopram (10 mg/day) or placebo for 3 months. Randomisation was done with permuted blocks stratified by centre, via a web-based system. The primary endpoint was the frequency of moderate or severe depressive symptoms (Montgomery-Åsberg Depression Rating Scale [MADRS] ≥16). Endpoints were assessed at 3 months after randomisation in the full analysis set (patients who took study medication and underwent assessment of primary endpoint after randomisation), in all patients who were enrolled and randomly assigned (intention to treat), and in all patients who completed the trial (per-protocol analysis). This trial is registered withClinicalTrials.gov, numberNCT01278498 . Findings: Between Jan 27, 2011, and June 30, 2014, 478 patients were assigned to placebo (n=237) or escitalopram (n=241); 405 were included in the full analysis set (195 in the placebo group, 210 in the escitalopram group). The primary outcome did not differ by study group in the full analysis set (25 [13%] patients in the placebo group vs 27 [13%] in the escitalopram group; odds ratio [OR] 1·00, 95% CI 0·56–1·80; p>0·99) or in the intention-to-treat analysis (34 [14%] vs 35 [15%]; OR 1·01, 95% CI 0·61–1·69, p=0·96). The study medication was generally well tolerated; the most common adverse events were constipation (14 [6%] patients who received placebo vs 14 [6%] who received escitalopram), muscle pain (16 [7%] vs ten [4%]), and insomnia (12 [5%] vs 12 [5%]). Diarrhoea was more common in the escitalopram group (nine [4%] patients) than in the placebo group (two [1%] patients). Interpretation: Escitalopram did not significantly reduce moderate or severe depressive symptoms in patients with acute stroke. Funding: Dong-A Pharmaceutical and Ministry for Health, Welfare, and Family Affairs, South Korea.